(untitled) (Modern education and development, 2024)
Ushbu maqolada konstitutsiyaning huquq va erkinliklarni taminlashdagi o‘rni, mamlakat taraqqiyotida tutgan ahamiyati ochib berilgan. В данной статье раскрывается роль конституции в обеспечении прав и свобод и ее значение в развитии страны. This article reveals the role of the constitution in ensuring rights and freedoms and its importance in the development of the country.